SEISMIC RATE CHANGE ANALYSIS BASED ON SPATIAL DISTRIBUTION OF SEISMOTECTONICS IN NORTHERN SUMATRA - Vicky Fikrotu Zakiyah; S Syafriani (PILLAR OF PHYSICS, 2021)
The northern Sumatra has a high level of seismic activity. Before a significant earthquake occurs, there is a seismic quiescence phenomenon that precedes a significant earthquake.This phenomenon can be observed in seismic rate changes based on the spatial distribution of z-value.The data used are from the NEIC/USGS website, period 1990-2021. The study was conducted in five focus zones, three zones in the 2004 (9.2 SR), 2005 (7.8 SR) 2010 (7.1 SR) earthquake, two zones with coordinates 0.6-1.8 North Latitude and 96.8-97.6 East Longitude and zones with coordinates 3.6-4.8 North Latitude and 97.8-98.6 East Longitude. Using the z-value spatial distribution method, the region is divided into several grids. Z-value is calculated for each grid and describes the seismic rate change in the northern Sumatra. Based on the results obtained, before the 2004, 2005, and 2010 earthquake events, there was a seismic quiescence phenomenon that preceded the earthquake event. The seismic quiescence phenomenon appears afew years in early 2021 in a zone that has high seismic activity. Meanwhile, in zones that have low seismic activity, the increase seismic activity appears six years before the beginning of 2021. The spatial distribution of z-values in early 2021, there is a phenomenon of a decrease in seismic activity in several areas of northern Sumatra.